BASED TO CLINICAL CASE. VON HIPLEA-LINDAU SYNDROME - Brzeziński Piotr (Our Dermatology Online, 2011)
von Hippel-Lindau syndrome (VHL) is a rare, genetic multi-system disorder characterized by the abnormal growth of tumors in certain parts of the body (angiomatosis). The tumors of the central nervous system (CNS) are benign and are comprised of a nest of blood vessels and are called hemangioblastomas. Hemangioblastomas may develop in the brain, the retina of the eyes, and other areas of the nervous system. Other types of tumors develop in the adrenal glands, the kidneys, or the pancreas. Symptoms of VHL vary among patients and depend on the size and location of the tumors. Symptoms may include headaches, problems with balance and walking, dizziness, weakness of the limbs, vision problems, and high blood pressure. Cysts (fluid-filled sacs) and/or tumors (benign or cancerous) may develop around the hemangioblastomas and cause the symptoms listed above. Individuals with VHL are also at a higher risk than normal for certain types of cancer, especially kidney cancer. Based on the case of 30-year old patient with characteristics of von Hippel-Lindau syndrome as phakomatosis.